Editorial Vol.4(2) - Dixit, Siddharth (Journal of Nepalese Prosthodontic Society, 2021)
Things have been difficult for the past year with the global pandemic. Still, with a better understanding of the disease and efficient management at the government and public level, we look better prepared and slowly returning to normalcy. We are finally open to all forms of treatment, of course with caution. Cheers!!On behalf of our editorial team, I am glad to present the Journal of Nepalese Prosthodontic Society (JNPS) Volume 4, Number 2. The journal established in 2018 has published 8 issues, including this latest offering. Through these initial years of our publication, we hope we have been able to provide a platform to share innovation, research, and ideas not only with our fellow prosthodontists but with our budding undergraduates and postgraduate students likewise.Finally, I would like to thank the editors, anonymous reviewers, our valuable readers, and contributors/authors for their continuous support and encouragement.Thank you.Dr. Siddharth DixitEditor in Chief